2017
DOI: 10.1017/s000711451700112x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in renal transplant recipients living in a low-latitude city: association with body fat, cardiovascular risk factors, estimated glomerular filtration rate and proteinuria

Abstract: Recent evidence suggests that vitamin D deficiency is associated with CVD, impaired kidney function and proteinuria. To date, no study has evaluated these associations in renal transplant recipients (RTR) adjusting for body adiposity assessed by a 'gold standard' method. This study aimed to evaluate the vitamin D status and its association with body adiposity, CVD risk factors, estimated glomerular filtration rate (eGFR) and proteinuria in RTR, living in Rio de Janeiro, Brazil (a low-latitude city (22°54'10"S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Out of these 196 articles 40 were eligible for full-text analysis. Ultimately, sixteen articles were included in this review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Figure 1 ). The rest of the articles were excluded as the design, protocol and/or methodology used investigated a different PICO question to those of our study.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these 196 articles 40 were eligible for full-text analysis. Ultimately, sixteen articles were included in this review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Figure 1 ). The rest of the articles were excluded as the design, protocol and/or methodology used investigated a different PICO question to those of our study.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our observations, the authors show that fat tissue amount and BMI are independent factors affecting 25(OH)D level, but this was not observed for eGFR or proteinuria [ 28 ]. Excess fat tissue, particularly indexes of obesity, were found to be strongly associated with vitamin D insufficiency among Brazilians after KTx [ 29 ]. They showed that patients with either vitamin D deficiency or insufficiency had significantly higher values of body fat and greater weight gain since transplantation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excess fat tissue, particularly indexes of obesity, were found to be strongly associated with vitamin D insufficiency among Brazilians after KTx [ 29 ]. They showed that patients with either vitamin D deficiency or insufficiency had significantly higher values of body fat and greater weight gain since transplantation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marchal et al established a significant association between lower 25VD and vascular calcification after KT [85]. However, a more recent study did not find a relationship between VD status and post-transplant hypertension and major CV events [97]. One of the aims of the already mentioned trial VITALE is to assess the effect of cholecalciferol supplementation on blood pressure control and CVD rates in KTRs [96].…”
Section: Vd Pleiotropy After Kt: Cardiovascular Diseasementioning
confidence: 99%